The Influence of Profitability and Leverage on Tax Aggressiveness (Empirical Study on LQ45 Companies in 2022-2024) - Nika Esti Rahayu; Rosida Ibrahim; Asri Primasiwi; Ghea Fauziah; Ika Sebti Nurkumalasari (Journal of Social Science and Humanities, 2025)
This study aims to analyze the effect of profitability and leverage on tax aggressiveness in companies listed in the LQ45 index during the 2022–2024 period. Tax aggressiveness is measured using the Effective Tax Rate (ETR), profitability is measured by Return on Assets (ROA), and leverage is measured using the Debt to Equity Ratio (DER). The sample was selected using purposive sampling, resulting in 72 observations. Data analysis was performed using multiple linear regression with E-Views 12. The results show that both profitability and leverage have no significant effect on tax aggressiveness, either partially or simultaneously. The coefficient of determination (R²) of 0.013631 indicates that only 1.36% of the variation in tax aggressiveness can be explained by profitability and leverage, while the remaining 98.64% is influenced by other factors outside the model. These findings suggest that the level of profit and debt does not determine tax aggressiveness behavior, as managerial decisions are more influenced by factors such as corporate governance, creditor supervision, as well as considerations of reputation and legal risk.